Household cockroaches carry CTX-M-15-, OXA-48- and NDM-1-producing enterobacteria, and share beta-lactam resistance determinants with humans - Noah Obeng-Nkrumah; Appiah-Korang Labi; Harriet Blankson; Georgina Awuah-Mensah; Daniel Oduro-Mensah; Judelove Anum; James Teye; Solomon Dzidzornu Kwashie; Evariste Bako; Patrick Ferdinand Ayeh-Kumi; Richard Asmah (BMC Microbiology, 2019)
Abstract Background This study was designed to investigate whether household cockroaches harbor cephalosporin-resistant enterobacteria that share resistance determinants with human inhabitants. From February through July 2016, whole cockroach homogenates and human fecal samples from 100 households were cultured for cephalosporin-resistant enterobacteria (CRe). The CRe were examined for plasmid-mediated AmpC, ESBL, and carbapenemase genes; antibiotic susceptibility patterns; and conjugative transfer of antibiotic resistance mechanisms. Clonal associations between CRe were determined by multi-locus sequence typing (MLST). Results Twenty CRe were recovered from whole cockroach homogenates from 15 households. The prevalence of households with cockroaches that harbored CRe, AmpC- (based on phenotype, with no identifiable blaAmpC genes), ESBL-, and carbapenemase-producers were 15, 4, 5%(2 bla CTX-M-15/TEM-1; 1 bla CTX-M-15/TEM-4; 1 bla TEM-24; 1 bla SHV-4) and 3%(2 bla NDM-1 genes and 1 bla OXA-48 gene), respectively. Overall, 20 CRe were recovered from 61 fecal samples of inhabitants from all 15 households that had cockroach samples positive for CRe. Of these, 5CRe (1 per household) were positive for ESBLs (bla TEM-24, bla TEM-14, bla CTX-M-15/TEM-4, bla SHV-3, bla CTX-M-15/TEM-1) and none carried AmpCs or carbapenemases. From 4% of households, the pair of cockroach and human CRe shared the same sequence type (ST), clonal complex (CC), antibiogram, and conjugable bla gene sequence (house 34, E. coli ST9/CC20-bla TEM-4; house 37, E. coli ST44/CC10-bla CTX-15/TEM-4; house 41, E. coli ST443/CC205-bla CTX-15/TEM-1; house 49, K. pneumoniae ST231/CC131-bla SHV-13). Conclusion The findings provide evidence that household cockroaches may carry CTX-M-15-, OXA-48- and NDM-1-producers, and share clonal relationship and beta-lactam resistance determinants with humans.